2022
DOI: 10.1038/s41581-022-00633-5
|View full text |Cite
|
Sign up to set email alerts
|

Trained immunity — basic concepts and contributions to immunopathology

Abstract: Trained immunity is a functional state of the innate immune response and is characterized by long-term epigenetic reprogramming of innate immune cells. This concept originated in the field of infectious diseases — training of innate immune cells, such as monocytes, macrophages and/or natural killer cells, by infection or vaccination enhances immune responses against microbial pathogens after restimulation. Although initially reported in circulating monocytes and tissue macrophages (termed peripheral trained im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 190 publications
2
127
0
Order By: Relevance
“…Trained immunity represents a functional state of the innate immune cells and tissue-resident stem cells adjusting their response to subsequent insults, characterized particularly by a prolonged activation after a resting period, orchestrated mainly by epigenetic reprogramming and the metabolic rewiring of cells [ 24 ]. It describes a property of innate immune system to mount memory-like responses against past microbial and non-microbial challenges [ 20 , 21 , 24 ].…”
Section: Trained Immunitymentioning
confidence: 99%
See 4 more Smart Citations
“…Trained immunity represents a functional state of the innate immune cells and tissue-resident stem cells adjusting their response to subsequent insults, characterized particularly by a prolonged activation after a resting period, orchestrated mainly by epigenetic reprogramming and the metabolic rewiring of cells [ 24 ]. It describes a property of innate immune system to mount memory-like responses against past microbial and non-microbial challenges [ 20 , 21 , 24 ].…”
Section: Trained Immunitymentioning
confidence: 99%
“…Trained immunity represents a functional state of the innate immune cells and tissue-resident stem cells adjusting their response to subsequent insults, characterized particularly by a prolonged activation after a resting period, orchestrated mainly by epigenetic reprogramming and the metabolic rewiring of cells [ 24 ]. It describes a property of innate immune system to mount memory-like responses against past microbial and non-microbial challenges [ 20 , 21 , 24 ]. To date, studies have shown that trained immunity can be maintained in innate immune cells for months up to decades, a process occurring in the bone marrow progenitor cells–central trained immunity, or for days up to a week in circulating innate immune cells–peripheral training [ 21 , 49 , 50 , 51 , 52 ].…”
Section: Trained Immunitymentioning
confidence: 99%
See 3 more Smart Citations